Investigation of Photo(electro)catalytic water splitting to evolve H2 on Pt-g-C3N4 nanosheets. (30th July 2022) - Wang, Yixuan; Sun, Jianpeng; Yao, Yuan; Li, Zizhen; Meng, Xiangchao
Abstract: g-C3 N4 has shown great potentials in photocatalytic water splitting to produce hydrogen. Herein, we successfully synthesized g-C3 N4 nanosheets via exfoliating bulk g-C3 N4 . And different metal nanoparticles were photo-deposited onto the surface of g-C3 N4 nanosheets. The photocatalytic H2 production activity of g-C3 N4 nanosheets increased from 0 to 11.2 μmol/h/gcat . The Pt loaded g-C3 N4 nanosheets manifested the highest H2 production activity with a rate of 589.4 μmol/h/gcat . In addition, the hydrogen evolution rate was further enhanced with addition of external bias to fabricate a photoelectrocatalytic (PEC) system. And the maximum hydrogen production rate (23.1 mmol/h/m 2 ) was obtained at a voltage of 0.6 V ( vs . Ag/AgCl). The enhancement in H2 production may be due to the following reasons: (1) Two-dimensional atomic flakes is beneficial to increase the specific surface area of g-C3 N4, enhance the mobility of carriers, and improve the energy band structure, (2) Pt nanoparticles play an important role in g-C3 N4 electron transport, (3) the g-C3 N4 nanosheets loaded with Pt nanoparticles exhibited significant enhancement in photoelectrocatalytic performance, which may be attributed to its enhanced electronic conductivity and photoelectrochemical surface area, (4) Pt inhibited the recombination of photogenerated carriers and significantly improved the photocatalytic performance. The enhancement mechanism was deeply discussed and explained in this work. Graphical abstract: Image 1 Highlights: The Pt-loaded C3 N4 nanosheets was synthesized. Pt0.3 -C3 N4 –N exhibited good photocatalytic activity for H2 production, with a rate of 589.4 μmol/h/gcat . Pt0.3 -C3 N4 –N showed good photoelectrocatalytic activity for H2 production, reaching 23.1 mmol/h/m 2 . Pt acts as a reservoir of photogenerated charge carriers, inhibiting its recombination.